Quantitative analysis of preferential utilization of AAV ITR as the packaging terminal signal - Li, Xin; Miller, Lohra Mickelle; Chrzanowski, Matthew; Tian, Jiahe; Jarrold, Martin F.; Herzog, Roland W.; Xiao, Weidong; Draper, Benjamin; Zhang, Junping (Frontiers in Bioengineering and Biotechnology, 2023)
Genetic engineering advances have led to recombinant adeno-associated virus (rAAV) becoming an invaluable tool for the development of effective gene therapies. The production of rAAV is susceptible to off-target heterogeneous packaging, the effects of which are still being understood. Here, rAAV with four genome lengths were produced using both adherent and suspension HEK293 cells to understand the 5' ITR termination. AAV8 vectors were produced from the Human FVIII plasmid for a full length 4707 nucleotides cargo with specific truncations creating smaller genomes. Conventionally, rAAV is characterized by differentiating empty from full capsids, but for this work, that description is incomplete. The small genomes in this study were characterized by charge detection mass spectrometry (CD-MS). Using CD-MS, packaged genomes in the range conventionally attributed to partials were resolved and quantified. In addition, alkaline gels and qPCR were used to assess the identity of the packaged genomes.Together these results showed a propensity for unit length genomes to be encapsidated. Packaged genomes occurred as replication intermediates emanating from the 5'ITR indicating HEK293 cells prefer unit-length genomes as opposed to the 5'ITR termination and heterogeneous DNA packaging observed previously from Sf9 cell systems. As both manufacturing processes are used and continually assessed to produce clinical material such an understanding will benefit rAAV design for basic research and gene therapy.